Implementasi Koordinasi Lintas Sektor dalam Rangka Pengendalian Leptospirosis di Kabupaten Jeneponto - Wirdayanti Wirdayanti; Syamsuar Manyullei; Muh. Fajaruddin Natsir (Hasanuddin Journal of Public Health, 2020)
Leptospirosis is an infectious disease caused by leptospira sp. and many are found in populations of people who live in rural areas. Leptospirosis is also a zoonotic disease that can be endemic and has adverse economic, social and psychological consequences. Zoonotic disease is closely related to human health, animals, and also the environment so that in controlling and preventing it is necessary the involvement or cooperation of various parties absolutely. This study was to determine cross-sectoral cooperation through coordination in the context of controlling leptospirosis in Jeneponto Regency. This type of research is qualitative with a phenomenological design. The number of informants in this study was 14 people. Determination of informants obtained by purposive sampling by determining the criteria for informants who are willing to be interviewed and play an important role in controlling infectious diseases. Showed that coordination between informants in the cross-sector had been carried out through the administration at the puskesmas conducted every quarter. Coordination conducted by the informant in controlling leptospirosis still needs to be improved, especially communication in the event of a case or outbreak in the community. The conclusion in this study is that cross-sectoral coordination needs to be improved, especially in controlling zoonotic diseases that occur in the community. The researchers suggest to the health center health workers to always coordinate well with other sectors that should be involved in controlling leptospirosis.